Football speed analysis and game analysis by using image processing - Filzah ‪Lina, Mohd Safeiee (2015)
The Football Speed and Game Analysis by using Image Processing is a real-time system that is used to detect, track a football and analyses the speed of the moving ball. The system is used mainly to help in data analysis of a football player by allowing the calculations of the speed of a moving ball to know how the power of the kicking that a football player has. This project more focuses on short distance kicking and on a stationary mode. This project provides the detailed steps on designing a real-time detection, tracking and analyzing system and considerations involved when designing it. Considerations such as ball detection, tracking, computer software, camera specification and tracking capabilities were taken. To be useful in football analysis of the ball speed has be recorded. The system works by using OpenCV. OpenCV is an imaging processing system that can be used by programming with C++ language. A pair of cameras was used. The cameras is used to capture the images or videos of the player while running on OpenCV. As for the analysis, a simple formula for finding speed was used and programmed into the system.